Effect of production environment, genotype and process on the mineral content of native bitter potato cultivars converted into white chuño - Haan, Stef de; Burgos, G.; Ccanto, Raul I.; Arcos, J.; Scurrah, M.; Salas, E.; Bonierbale, Merideth W. (Wiley, 2012)
BACKGROUND: Variables and interaction effects affecting the mineral concentration of Andean bitter potatoes converted into so‐called white chuño are unknown. We report on the effect of three contrasting production environments (E) on the dry matter (DM), zinc, iron, calcium, potassium, magnesium, phosphorus and sodium concentration of four potato native bitter genotypes (G) processed (P) into two different ‘types’ of white chuño.RESULTS: The DM content and iron, calcium, magnesium and sodium concentration of white chuño are significantly dependent on E, G, P, and E × G × P interaction (predominantly at P < 0.01). In particular, the DM content and calcium concentration are influenced by all variables and possible interaction effects. The zinc and potassium concentration are not significantly dependent on E × G, G × P or E × G × P interaction effects, while the phosphorus concentration is not significantly affected by the G × P or E × G × P interaction effect. Zinc, phosphorus and magnesium concentrations decrease in the ranges of 48.3–81.5%, 61.2–73.0% and 62.0–89.7% respectively. The decrease in potassium is particularly severe, with 122‐ to 330‐fold losses. Iron and calcium increase by 11.2–45.6% and 74.5–714.9% respectively.CONCLUSION: E, G, P, and various interaction effects influence the mineral concentration of traditionally processed tubers. We speculate that mineral losses are caused by leaching, while increases of iron and calcium are a likely result of absorption. Copyright © 2012 Society of Chemical Industry